2015
DOI: 10.1007/s00701-014-2331-2
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 regulation and TUNEL-positive cell death differ between genders in the secondary inflammatory response following experimental penetrating focal brain injury in rats

Abstract: COX-2 regulation differed between genders after TBI. The increased COX-2 expression in male rats correlated with increased apoptotic cell death detected by increased TUNEL staining at 24 h, but not with neuronal necrosis measured by Flouro-Jade. Astrogliosis and microgliosis did not differ, confirming a comparable level of trauma. The gender-specific trait of the secondary inflammatory response may be connected to prostaglandin regulation, which may partially explain gender variances in outcome after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 44 publications
5
34
1
Order By: Relevance
“…Thus, lower COX-2 expression and activity has been noted in the macula densa of female rats compared to males, contributing to the major protection of female to the blood pressure increment and renal damage 30 . Moreover, the inferior susceptibility to traumatic brain injury of male versus female rats has been related to a robust higher expression of COX-2 in the brain of male rats 31 . In addition, long-term testosterone treatment augmented COX-2 levels in male rat brain blood vessels, whereas treatment of male rats with 17β-estradiol significantly impaired cerebrovascular COX-2 levels after an inflammatory stimulus 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lower COX-2 expression and activity has been noted in the macula densa of female rats compared to males, contributing to the major protection of female to the blood pressure increment and renal damage 30 . Moreover, the inferior susceptibility to traumatic brain injury of male versus female rats has been related to a robust higher expression of COX-2 in the brain of male rats 31 . In addition, long-term testosterone treatment augmented COX-2 levels in male rat brain blood vessels, whereas treatment of male rats with 17β-estradiol significantly impaired cerebrovascular COX-2 levels after an inflammatory stimulus 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the data are limited, microglia may have sex‐specific responses to TBI in animal models. Gunther et al () demonstrated sex differences in COX‐2 regulation after a penetrating brain injury in male and female rats; however, they found no difference in microglial activation between sexes in the perilesional area or contralateral side. There is conflicting evidence about the influence of sex hormones on the microglial response after TBI (Barreto et al, ; Bruce‐Keller et al, ; Acaz‐Fonseca et al, ).…”
Section: Sex Differences In Microglial Activation and Tbimentioning
confidence: 99%
“…Gunther et al (), using a penetrating brain injury model, found that male rats had an increased COX‐2 response compared with females at 24 and 72 hr, which was associated with increased inflammation. Furthermore, inducible nitric oxide synthase (iNOS) expression in the perilesional area was significantly higher in female rats than in males, but there was no difference in iNOS expression in the ipsilateral cortex or contralateral side between sexes (Gunther et al, ).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Inflammatory reactions and cell death after TBI can be different in males and females (Gunther et al, 2015). Role of biomarkers in PTSD and mTBI 5…”
Section: Clinicalmentioning
confidence: 99%